PERSISTENT ORGANIC POLLUTANS (POPS) DAN KONVENSI STOCKHOLM - Lina Warlina (Jurnal Matematika Sains dan Teknologi, 2009)
Persistent organic pollutants (POPs) are toxic chemicals that adversely affect human health and the environment around the world. Because they can be transported by wind and water, most POPs generated in one country can affect people and wildlife far from where they are used and released. They persist for long periods of time in the environment and can accumulate and pass from one species to the next through the food chain. To address this global concern, many countries in the world joined forces with 90 other countries and the European Community to sign a groundbreaking United Nations treaty in Stockholm, Sweden, in May 2001, known as the Stockholm Convention. One of important agreement is all countries agreed to reduce or eliminate the production, use, and/or release of 12 key POPs. The Convention specifies a scientific review process that could lead to the addition of other POPs chemicals of global concern. POPs include a range of substances that include intentionally produced chemicals currently or once used in agriculture, disease control, manufacturing, or industrial processes. Also it can be produced by unintentionally produced chemicals, such as dioxins, that result from some industrial processes and from combustion (for example, municipal and medical waste incineration and backyard burning of trash).